(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Generation is understood as the “identifiable group that shares birth years, age, location, and significant life events at critical developmental stages”. Corporate have seen many generations at work and each of the generations have displayed many different traits and characteristics. When it comes to managing the performances of individual employees, it becomes imperative for the manager or the supervisor to understand each employee and their behavior. Thus one such demarcation of traits can be understood by the generation they belong to. This research article deals with the critical traits of Gen Z employees, their strengths and weakness and discusses that based on their traits the performances could be managed appropriately well.